Educational insights into digital entrepreneurship: the influence of personality and innovation attitudes - João M. Lopes; Sofia Gomes; Elisabete Nogueira (Journal of Innovation and Entrepreneurship)
Abstract Digital entrepreneurship implies a radical transformation of economic paradigms, allowing new entrepreneurs to create a more sustainable, creative, and connected future. This study explores the influence of higher education students’ personality traits on their innovative digital attitude and digital entrepreneurial intention. It also explores the moderating role of digital entrepreneurial education in the relationship between innovative digital attitude and digital entrepreneurial intention. To this end, a sample of 417 higher education students residing in Portugal was collected through a questionnaire made available online, and the partial least square method was applied to a formulated research model. The results reveal that an innovative digital attitude positively influences the digital entrepreneurial intention of higher education students in Portugal. The Big-Five personality traits directly affect innovative digital attitudes but not their digital entrepreneurial intention. However, this relationship becomes significant when the relationship between personality traits and digital entrepreneurial intention is mediated by an innovative digital attitude. Furthermore, the intensifying role of digital entrepreneurial education was demonstrated in converting students' innovative digital attitudes into their digital entrepreneurial intention. Thus, this study indicates that personality traits, which are still scarcely addressed in entrepreneurship, can be an explanation of innovative digital attitudes and predictors of digital entrepreneurial intention, as well as the important role of digital entrepreneurial education in boosting digital entrepreneurship.